Strategi Adaptasi Pembelajaran Sensori pada Anak yang Telah Menguasai Calistung: Studi Kasus TK PGRI Tunas 83 Cibadak Sukabumi - Muhtar, Lutpiah; Anggraeni, Riska; Hikmah , Rezqia Sakinatul; Mulyani, Sri; Muttaqin, Yasyfina Auliya (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This research aims to examine the adaptation strategies of sensory learning for children who have mastered basic literacy and numeracy skills at TK PGRI Tunas 83 Cibadak Sukabumi. Using a qualitative approach with a case study method, this research involved 5 teachers, 8 students, and 8 parents as informants. Data collection was conducted through participatory observation, in-depth interviews, and documentation. The results show that sensory learning adaptation strategies integrated with literacy and numeracy skills successfully maintain learning interest and optimize children's development. The implementation of these strategies includes the use of various sensory media in literacy and numeracy learning, development of sensory-based enrichment activities, and integration of sensory learning in project activities. The main challenges in implementation include the need for thorough planning and teacher creativity in activity development. This research recommends the importance of developing teacher competencies and strengthening collaboration between schools and parents in supporting the success of learning adaptation strategies